2012
DOI: 10.1111/j.1476-5381.2012.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic acid phenethyl ester protects nigral dopaminergic neurons via dual mechanisms involving haem oxygenase‐1 and brain‐derived neurotrophic factor

Abstract: BACKGROUND AND PURPOSECaffeic acid phenethyl ester (CAPE) is a component of honey bee propolis that can induce expression of haem oxygenase-1 (HO-1). Because HO-1 induction has been suggested to protect dopaminergic neurons in the substantia nigra, we examined the effect of CAPE in experimental models of dopaminergic neurodegeneration. EXPERIMENTAL APPROACHNeuroprotective effect of CAPE was investigated in rat organotypic midbrain slice cultures and in vivo, using a mouse model of dopaminergic neurodegeneratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 62 publications
(93 reference statements)
2
49
0
Order By: Relevance
“…These proteins have been associated with differentiation and neurite outgrowth in PC12 cells (Das et al, 2004) and up-regulation of them have been found in PC12 cells stimulated with NGF (Romano et al, 1987;Van Hooff et al, 1986). Therefore, our study is in line with previous studies which demonstrated (i) that CAPE protects nigral dopaminergic neurons via induction of brain-derived neurotrophic factor (BDNF) (Kurauchi et al, 2012) and (ii) induces the expression of NGF and p75 neurotrophin receptor (p75 NTR ) in C6 glioma cells (Lin et al, 2010b). NGF binding to p75 NTR has been associated with both neuronal survival and death, and the balance of these opposing effects is important in the development, maintenance and regeneration of the nervous system (Yamashita et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…These proteins have been associated with differentiation and neurite outgrowth in PC12 cells (Das et al, 2004) and up-regulation of them have been found in PC12 cells stimulated with NGF (Romano et al, 1987;Van Hooff et al, 1986). Therefore, our study is in line with previous studies which demonstrated (i) that CAPE protects nigral dopaminergic neurons via induction of brain-derived neurotrophic factor (BDNF) (Kurauchi et al, 2012) and (ii) induces the expression of NGF and p75 neurotrophin receptor (p75 NTR ) in C6 glioma cells (Lin et al, 2010b). NGF binding to p75 NTR has been associated with both neuronal survival and death, and the balance of these opposing effects is important in the development, maintenance and regeneration of the nervous system (Yamashita et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Antioxidants such as resveratrol, caffeic acid, epicatechin ECGC can activate hormetic pathways in neurons and mediate cytoprotection by activating anti-apoptotic proteins (Chen et al, 2005; Kurauchi et al, 2012; Mandel et al, 2008; Ren et al, 2011; Schroeter et al, 2007). For instance, a redox-sensitive transcription factor NF-E2-related factor-2 (Nrf2) is released from the cytosolic repressor protein Keap1 (Kelch ECH associating protein) under oxidative stress, translocates to the nucleus and binds to the antioxidant-response element (ARE), thus activating antioxidant defense enzymes, including glutathione S-transferase, glutathione peroxidase (GPx) and heme oxygenase-1 (HO-1) (Lee and Johnson, 2004).…”
Section: Translational Research Opportunities and Challengesmentioning
confidence: 99%
“…mp 153−155°C; IR (KBr) ν max 3488, 3346, 1649, 1602, 1551, 1326, 1287, 1189 cm −1 ; 1 H NMR (400 MHz, CDCl 3 ) δ 7.34 (1H, d, J = 16.0 Hz, H-β), 7.13−7.24 (5H, m, H-2′, 3′, 4′, 5′, 6′), 6.93 (1H, d, J = 1.6 Hz, H-2), 6.82 (1H, dd, J = 1.6, 8.4 Hz, H-6), 6.71 (1H, d, J = 8.4 Hz, H-5), 6.16 (1H, d, J = 16.0 Hz, H-α), 3.48 (2H, t, J = 7.2 Hz, H-α′), 2.78 (2H, t, J = 7.2 Hz, H-β′); HRESIMS [M − H] − m/z 282.1125 (Calcd for C 17 H 16 NO 3 , 282.1130).Caffeic Acid 4-Hydroxyphenylacetamide(17). The title compound was prepared according to method C as light yellow powder (35 mg, 11.7% yield).mp 211−212°C; IR (KBr) ν max 3369, 1646, 1604, 1516, 1241 cm −1 ; 1 H NMR (400 MHz, CD 3 OD) δ 7.37 (1H, d, J = 15.6 Hz, H-β), 7.05 (2H, d, J = 8.4 Hz, H-2′, 6′), 6.99 (1H, d, J = 2.0 Hz, H-2), 6.89 (1H, dd, J = 2.0, 8.4 Hz, H-6), 6.75 (1H, d, J = 8.4 Hz, H-5), 6.70 (2H, d, J = 8.4 Hz, H-3′, 5′), 6.33 (1H, d, J = 15.MHz, CD 3 OD) δ 7.52 (1H, d, J = 16.0 Hz, H-β), 7.03 (1H, d, J = 2.0 Hz, H-2), 6.94 (1H, dd, J = 2.0, 8.0 Hz, H-6), 6.78 (1H, d, J = 8.0 Hz, H-5), 6.70 (1H, d, J = 2.0 Hz, H-2′), 6.70 (1H, d, J = 8.0 Hz, H-5′), 6.58 (1H, dd, J = 2.0, 8.0 Hz, H-6′), 4.29 (2H, t, J = 7.2 Hz, H-α′), 2.84 (2H, t, J = 7.2 Hz, H-β′); HRESIMS [M − H] − m/z 315.0862 (Calcd for C 17 H 15 O 6 , 315.0869).…”
mentioning
confidence: 99%